FORMULATION AND TEST OF ANTIOXIDANT ACTIVITY OF GEL MASK PEEL OFF FROM SURIAN (Toona Sinensis) LEAF ETHANOL EXTRACT IN VITRO - Uce Lestari; Muhaimin Muhaimin; Yuliawati Yuliawati (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Free radicals can cause damage to skin oxidative cells which will have an impact on aging. This can be shown by the appearance of wrinkles, dull looking skin, black spots (spots) and easily dry skin texture. Antioxidants are compounds that can overcome the bad effects of free radicals. The use of the effects of antioxidants for preparations aimed at facial skin, is better if it is made with cosmetic dosage forms for topical use compared to oral use. One example of this cosmetic preparation is the peel off gel mask. One source of antioxidants comes from the ethanol extract of surian leaves. The aim of the study was to make a gel peel off mask preparation containing antioxidants from surian leaf extract. Surian leaves were extracted by maceration using ethanol, the antioxidant test used the DPPH method. The formulation of peel off gel masks used various extract concentrations, namely 2.5%; 5% ; 7.5% and 10% . Tests for physical characteristics have met the requirements of SNI with organoleptic covering brownish clear color, characteristic aromatic odor of surian leaves, thick form. pH value (4.87-5.47), Viscosity (14088.16-44722.81 cps), spreadability (5.26-5.69 cm), adhesion power (4.08-4.56 seconds) and drying power (22.58-24.02 minutes). The peel off gel mask with the best antioxidant value is formulation 5.